2013
DOI: 10.1097/iae.0b013e31826f065e
|View full text |Cite
|
Sign up to set email alerts
|

Costs of Newly Diagnosed Neovascular Age-Related Macular Degeneration Among Medicare Beneficiaries, 2004–2008

Abstract: Newly diagnosed neovascular age-related macular degeneration was associated with a substantial increase in total medical costs. Costs increased over time, reflecting growing use of anti-vascular endothelial growth factor therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Our review identified 13 studies that reported on the costs associated with the introduction of anti-VEGF treatments for the treatment of nAMD [41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Impact On Costsmentioning
confidence: 99%
“…Our review identified 13 studies that reported on the costs associated with the introduction of anti-VEGF treatments for the treatment of nAMD [41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Impact On Costsmentioning
confidence: 99%
“… 5 6 The ongoing nature of treatment for neovascular AMD has profound cost implications to patients and to society, reflected in the recent retrospective observational study that demonstrated that new cases of neovascular AMD were associated with substantial discrepancies in total medical costs (41% higher compared with non-neovascular AMD controls). 7 The cost implications for neovascular AMD treatment are, however, balanced against savings associated with this treatment (improvement in visual acuity and reduction in cases of legal blindness). 8 Patients with untreated or untreatable advanced AMD invariably suffer from impairment of central vision, with consequential loss of social independence as a result of a concomitant inability to read, recognise faces, watch television or drive.…”
Section: Introductionmentioning
confidence: 99%
“…The 1-year cost increase for AF was high, even relative to the 1-year cost of other known costly conditions such as heart failure, estimated at an incremental US$12,924 in 2006 dollars (US$14,423 in 2009 dollars) in the CHS 26 or macular degeneration (US$5197 in 2009 dollars); 27 but the total hospital and clinical costs were still higher among participants dying of or surviving with prostate cancer 28 (US$45,053 in 2009 dollars in medical costs, compared to US$25,675 in the year post-AF diagnosis).…”
Section: Discussionmentioning
confidence: 99%